Recurrent venous thromboembolism patients form clots with lower elastic modulus than those formed by patients with non‐recurrent disease. (8th March 2019) - Baker, Stephen R.; Zabczyk, Michal; Macrae, Fraser L.; Duval, Cédric; Undas, Anetta; Ariëns, Robert A. S.
Abstract : Essentials Venous thromboembolism (VTE) recurrence leads to decreased clot elastic modulus in plasma. Recurrent VTE is not linked to changes in clot structure, fiber radius, or factor XIII activity. Other plasma components may play a role in VTE recurrence. Prospective studies should resolve if clot stiffness can be used as predictor for recurrent VTE. Summary: Background: Venous thromboembolism (VTE) is associated with a high risk of recurrent events after withdrawal of anticoagulation. Objectives: To determine the difference in plasma clot mechanical properties between patients with recurrent VTE (rVTE) and those with non‐recurrent VTE (nrVTE). Methods: We previously developed a system for determining clot mechanical properties by use of an in‐house magnetic tweezers system. This system was used to determine the mechanical properties of clots made from plasma of 11 patients with rVTE and 33 with nrVTE. Plasma was mixed with micrometer‐sized beads, and thrombin and calcium were added to induce clotting; the mixture was then placed in small capillary tubes, and clotting was allowed to proceed overnight. Bead displacements upon manipulation with magnetic forces were analyzed to determine clot elastic and viscous moduli. Fibrin clot structure was analyzed with turbidimetry and confocal microscopy. Factor XIII was measured by pentylamine incorporation into fibrin. Results: Clots from rVTE patients showed nearly two‐fold less elastic and less viscous moduli than clots from nrVTE patients, regardless of male sex, unprovoked events, family history of VTE, fibrinogen concentration, or body mass index. No differences were observed in clot structure, fibrinolysis rates, or FXIII levels. Conclusion: Using magnetic tweezers for the first time in patient samples, we found that plasma clots from rVTE patients showed a reduced elastic modulus and a reduced viscous modulus as compared with clots from nrVTE patients. These data indicate a possible role for fibrin clot viscoelastic properties in determining VTE recurrence.